Determinan Indeks Saham Syariah Determinants of the Indonesian Sharia Stock Index Using the Vector Error Correction Model (VECM) Approach - Ritonga, Afiq Yasfa Assaumi; Imsar, Imsar; Harahap, Muhammad Ikhsan (Amkop Management Accounting Review (AMAR), 2025)
Various models of choices that people have to invest their capital in the form of investment, including by investing their capital in the capital market. ISSI is present as one of the stock indicators that displays all sharia stocks on the Indonesia Stock Exchange. The purpose of this study is to see the level of interaction between inflation, exchange rates, BI rates, oil prices, and gold, and how this impacts the Indonesian Sharia Stock Index (ISSI) in the short and long term from 2015 to 2024. This study uses a quantitative approach using the Vector Error Correction Model (VECM) method. The results of the VECM show three long-term variables—inflation, BI rates, and oil prices—and two short-term variables, namely gold prices and exchange rates. The results of the causality test show a two-way relationship between ISSI and the exchange rate. The results of the Variance Decomposition test show that oil prices make the largest contribution, namely 25.6 percent. followed by the exchange rate of 18.3 percent, inflation of 7.1 percent, BI rate of 6.9 percent and gold prices of 0.6 percent to the variation of ISSI. The results of the causality test show that the BI rate significantly affects the gold price, the oil price affects the exchange rate, the ISSI affects the exchange rate, and the exchange rate affects the ISSI. This confirms that the ISSI and the exchange rate have a strong causal relationship.